Distal hereditary motor neuronopathy of the Jerash type is caused by a novel SIGMAR1 c.500A>T missense mutation. Issue 3 (11th September 2019) - Ververis, Antonis; Dajani, Rana; Koutsou, Pantelitsa; Aloqaily, Ahmad; Nelson-Williams, Carol; Loring, Erin; Arafat, Ala; Mubaidin, Ammar Fayez; Horany, Khalid; Bader, Mai B; Al-Baho, Yaqoub; Ali, Bushra; et al.
Abstract : Background: Distal hereditary motor neuronopathies (dHMN) are a group of genetic disorders characterised by motor neuron degeneration leading to muscle weakness that are caused by mutations in various genes. HMNJ is a distinct form of the disease that has been identified in patients from the Jerash region of Jordan. Our aim was to identify and characterise the genetic cause of HMNJ. Methods: We used whole exome and Sanger sequencing to identify a novel genetic variant associated with the disease and then carried out immunoblot, immunofluorescence and apoptosis assays to extract functional data and clarify the effect of this novel SIGMAR1 mutation. Physical and neurological examinations were performed on selected patients and unaffected individuals in order to re-evaluate clinical status of patients 20 years after the initial description of HMNJ as well as to evaluate new and previously undescribed patients with HMNJ. Results: A homozygous missense mutation (c.500A>T, N167I) in exon 4 of the SIGMAR1 gene was identified, cosegregating with HMNJ in the 27 patients from 7 previously described consanguineous families and 3 newly ascertained patients. The mutant SIGMAR1 exhibits reduced expression, altered subcellular distribution and elevates cell death when expressed. Conclusion: In conclusion, the homozygous SIGMAR1 c.500A>T mutation causes dHMN of the Jerash type, possibly due to a significant drop of protein levels. This finding is in agreement with other SIGMAR1 mutations that have been associated with autosomal recessive dHMN with pyramidal signs; thus, our findings further support that SIGMAR1 be added to the dHMN genes diagnostic panel.